Unraveling the future of genomics: CRISPR, single-cell omics, and the applications in cancer and immunology - Menon, A. Vipin; Song, Bicna; Chao, Lumen; Sriram, Diksha; Chansky, Pamela; Bakshi, Ishnoor; Ulianova, Jane; Li, Wei (Frontiers in Genome Editing, 2025)
The CRISPR system has transformed many research areas, including cancer and immunology, by providing a simple yet effective genome editing system. Its simplicity has facilitated large-scale experiments to assess gene functionality across diverse biological contexts, generating extensive datasets that boosted the development of computational methods and machine learning/artificial intelligence applications. Integrating CRISPR with single-cell technologies has further advanced our understanding of genome function and its role in many biological processes, providing unprecedented insights into human biology and disease mechanisms. This powerful combination has accelerated AI-driven analyses, enhancing disease diagnostics, risk prediction, and therapeutic innovations. This review provides a comprehensive overview of CRISPR-based genome editing systems, highlighting their advancements, current progress, challenges, and future opportunities, especially in cancer and immunology.